CHILD MARRIAGE SANCTIONS: STUDY OF LEGISLATION IN MUSLIM COUNTRIES (Lex Jurnalica, 2020)
Marriage under the minimum age that is legally permitted by dispensation through a court permit should not be recognized as valid under the law, and there must be penalties (both civil and criminal sanctions) for parents and guardians. All of these policies can maintain the acceptance of child-age marriages and violate children's rights. As a result, underage marriages still occur and the implementation of penalties tends to be low so it does not cause a deterrent effect to the community. This study uses a comparative study of law in Muslim countries, namely Indonesia, Bangladesh, Pakistan, and Egypt. Based on that, this research is juridical research. So the main focus of this research is how the form of sanctions (both civil and criminal) for those who do underage marriages based on the law in the Muslim country. To change the situation of the child for the better by discussing legal issues regarding sanctions for those who marry underage.